Pengaruh Ion Hg(II) Terhadap Efektivitas Fotoreduksi Ion Cu(II) Terkatalisis TiO2 dalam Limbah Cair Industri Kerajinan Perak di Desa Ungga Kec. Praya Lombok Tengah - Hatimah, Husnul (Hydrogen: Jurnal Kependidikan Kimia, 2019)
In this study a study of the effect of TiO2 photocatalysts and Hg (II) ions in the wastewater of the silver industry in Ungga Village, Kec. PrayaKab. Central Lombok to the effectiveness of Cu (II) photoreduction which is catalyzed by TiO2. The photoreduction process is carried out by irradiating liquid waste containing Cu (II) and Hg (II) ions without or by adding TiO2 photocatalyst powder in a closed reactor equipped with UV light. The condition of the photoreduction process is 50 mL of silver waste containing Cu (II) and Hg (II) with a reaction time of 24 hours and a mass of TiO2 20 mg at 10 ppm Cu (II) ion concentration. Photoreduction results are determined based on the difference in the concentration of Cu (II) ions with the concentration of residual Cu (II) ions in silver waste without the addition of TiO2 photocatalysts. Furthermore, the data obtained compared to the results of Cu (II) photoreduction catalyzed by pure TiO2 laboratory scale. The amount of metal in the mixture was determined by the Atomic Absorption Spectrophotometry (AAS) method. The results showed that in silver handicrafts containing Cu (II) and Hg (II) ions the addition of TiO2 can increase the effectiveness of Cu (II) photoreduction from 6.57% to 33.38%, which begins with the adsorption process. Hg (II) in silver handicraft waste causes inter-metal reduction competition so that it can reduce the effectiveness of Cu (II) ion photoreduction catalyzed by TiO2 by 9.84% when compared to the percentage of Cu (II) ion Ti2O scale scale laboratory testing.